Review of access control mechanisms in cloud computing - Muhammad Rizwan, Ghori; Ahmed, Abdulghani Ali (Institute of Physics Publishing, 2018)
Cloud Computing is an evolving technology in the field of IT. People are using this technology vastly as it reduces the storage and other services burden of the users as they use the services provided by the cloud. There are many advantages related to this technology like unlimited storage, cost effectiveness but lacking the strong authentication process. Many researchers are working on the security issue of cloud like user confidentiality, integrity and authenticity etc. However, in this paper we have reviewed and discussed several papers that are related to the authentication in cloud environment. Moreover, after studying different authentication system made by the researchers, we have critically analysed them and found advantages and disadvantages along with some suggestions for the future work.